The roles of iodized oil-based lymphangiography and post-lymphangiographic computed tomography for specific lymphatic intervention planning in patients with postoperative lymphatic fistula: a literature review and case series - Pan, Fan; Loos, Martin; Do, Thuy; Richter, G. M.; Kauczor, Hans-Ulrich; Hackert, Thilo; Sommer, Christof-Matthias (CVIR endovascular, 2020)
In the management of patients with postoperative lymphatic fistula (LF) in different locations, iodized oil-based lymphangiography (LAG) from trans-pedal or intranodal route is an established diagnostic approach with the potential to plan further interventional treatments. However, specific lymphatic interventions are indicated depending on different locations and morphologies of the LF. After a systematic literature review, four types of interventions can be considered, including direct leakage embolization/sclerotherapy (DLE/DLS), percutaneous afferent lymphatic vessel embolization (ALVE), percutaneous afferent lymphatic vessels disruption/sclerotherapy (ALVD/ALVS), and trans-afferent nodal embolization (TNE). In the iodized oil-based LAG, three potential lymphatic targets including confined leakage, definite afferent LVs, and definite closest afferent LNs should be comprehensively assessed. For optimal prospective treatment planning for LF, iodized oil-based post-lymphangiographic computed tomography (post-LAG CT) is a useful complement to the conventional iodized oil-based LAG, which can be performed easily after LAG. This review article summarized the current evidence of the specific lymphatic interventions in patients with postoperative LF and explored the potential benefits of post-LAG CT in the intervention planning from a case series.
Gesehen am 21.08.2024